Answer:
its d
Step-by-step explanation:
Step-by-step explanation:
f(x) = 3x² - 2x + 7
f(-2) = 3(-2)² -2(-2) + 7
= 3(4) + 4 + 7
= 23
Sec^2 x - 1 = tan^2x
Proof:
Sec^2x = 1+ tan^2x
1/cos^2x = 1 + sin^2x/cos^2x
<span>1/cos^2x - sin^2x/cos^2x = 1
</span>Using common denominator:
(1-sin^2x)/cos^2x = 1
sin^2x + cos^2 x = 1
cos^2 x = 1 - sin^2x
Substituting :
cos^2x/<span>cos^2x = 1
</span>1 = 1
Left hand side = right hand side
1, ___, ____, _____, _____, _____, ____, 29
29-1 = 28
28/7 = 4
1, 5, 9, 13, 17, 21, 25, 29
Answer:
dude I ain't no albert einstein but I think it's 61
Step-by-step explanation:
stay groovy man